The Significance Of Population Migration As A Risk Factor For Cross-Border Importation Of Dangerous Infectious Diseases Into The Territory Of The Republic Of Uzbekistan - Kasimov Ilxamdjan Asamovich; Ulmasova Saodat Ilhomjon qizi (Peerian Journals Publishing, 2025)
This article examines certain types of external population migration as risk factors for the emergence of outbreaks of especially dangerous infectious diseases in the Republic of Uzbekistan and the Central Asian region. The role of tourism and labor-related cross-border migration in shaping the epidemic manifestations of infectious diseases is highlighted. The importation of influenza caused by new virus subtypes, cholera, poliomyelitis, hemorrhagic fevers, anthrax, brucellosis, and others is becoming increasingly relevant for these regions.
Keywords: migration; migrationespecially dangerous infectious diseases; Uzbekistan